Teoritikal Bentuk Bore Tsunami Menggunakan Metode Dambreak Dan Wavemaker Dengan Sistem DualSPHysics - Kartika Indah Sari; Yusrizal Lubis; Ditya Andrean Supit (Universitas Harapan Medan, 2022)
A tsunami is a large water wave with the impact of damage and destruction on facilities and infrastructure when it spreads to the mainland. In general, a tsunami approaching the coast forms a bore wave when a single uniform (solitary) wave in a tsunami breaks when it enters the coast. This research was conducted to determine the transition process of tsunami waves to form a bore, as well as to determine the characteristics of the tsunami bore shape. The bore tsunami research was carried out using the dambreak and wavemaker methods using the DualSPHysics simulation computational program, the dimensions of the open channel at the dambreak were 20.7 m x 1.43 m x 1.5 m. The beach modeling on the dambreak has dimensions of 12.7 m x 0.64 m with a slope of 1:20. The channel dimensions on the wavemaker are 135 m x 2 m x 5 m. The wavemaker beach model has dimensions of 60 m x 3 m with a slope of 1:20. The total number of particles in the dambreak simulation is 24,638,764. The simulation results provide information that the bore wave is the result of the transition of a solitary wave breaking as it approaches the shoreline. The wave height that was formed at the beginning of the formation will continue to increase in height until it approaches the shoreline